Mapeamento dos modos de transferência metálica na soldagem MIG de alumínio - Figueiredo, Kléber Mendes de (2002)
Among the aluminum welding processes, the MIG process is the preferred one, because it can be easily made self-operating, it has high productivity and great versatility regarding the material type and thickness in welding. The possibility to change the transfer mode to adapt to different thickness, joint types, among other aspects, another important and attractive feature. However, little is known about the transfer modes in the aluminum MIG welding. For this reason, in this study an analysis about the metal transfer modes in the aluminum welding was proposed. The objective of this study was to generate maps which could identify the metal transfer modes and their regions due to the shielding gas and the wire diameter. In this sense, it is expected that new information can contribute to the quality and productivity improvement of the aluminum MIG welding. The experimental procedure was the execution of weldings in aluminum plate in a flat position with the electronic source in a constant voltage and with variation of the voltage as well as the wire feed speed. So that the effect could be compared, the travel speed/wire feed speed ratio was maintained constant (were beads with the same volume maintained). Studies with wire of 1.0 mm and pure Ar and mixture Ar + 25% He and wire of 1.2 mm with pure Ar were carried out. The methodology used for recording and further analysis of the metal transfers was the laser Shadowgraphy combined with high speed recording machine (2000 scenes per second). Therefore, it was possible to design the maps with the three wire/gas combinations, when four metal transfer modes ( short circuit, globular, spray and globular/short circuit) and their respective transition zones were determined. Changes in the regions of the transfer modes were noticed when the gas and/or the wire diameter was altered. The maps also permitted to determine the transition current zones between the globular and the spray mode showing a zone for each tested situation.